Potential of Gallium as an Antifungal Agent - Bastos, Rafael Wesley; Rossato, Luana; Valero, Clara; Lagrou, Katrien; Colombo, Arnaldo Lopes; Goldman, Gustavo H. (Frontiers in Cellular and Infection Microbiology, 2019)
There are only few drugs available to treat fungal infections, and the lack of new antifungals, along with the emergence of drug-resistant strains, results in millions of deaths/year. An unconventional approach to fight microbial infection is to exploit nutritional vulnerabilities of microorganism metabolism. The metal gallium can disrupt iron metabolism in bacteria and cancer cells, but it has not been tested against fungal pathogens such as Aspergillus and Candida. Here, we investigate in vitro activity of gallium nitrate III [Ga(NO3)3] against these human pathogens, to reveal the gallium mechanism of action and understand the interaction between gallium and clinical antifungal drugs. Ga(NO3)3 presented a fungistatic effect against azole-sensitive and -resistant A. fumigatus strains (MIC50/90 = 32.0 mg/L) and also had a synergistic effect with caspofungin, but not with azoles and amphotericin B. Its antifungal activity seems to be reliant on iron-limiting conditions, as the presence of iron increases its MIC value and because we observed a synergistic interaction between gallium and iron chelators against A. fumigatus. We also show that an A. fumigatus mutant (ΔhapX) unable to grow in the absence of iron is more susceptible to gallium, reinforcing that gallium could act by disrupting iron homeostasis. Furthermore, we demonstrate that gallium has a fungistatic effect against different species of Candida ranging from 16.0 to 256.0 mg/L, including multidrug-resistant Candida auris, C. haemulonii, C. duobushaemulonii, and C. glabrata. Our findings indicate that gallium can inhibit fungal pathogens in vitro under iron-limiting conditions, showing that Ga(NO3)3 could be a potential therapy not only against bacteria but also as an antifungal drug.